Advantages of external quality assessment‐EQA programs. Issue 4 (12th April 2022) - Montalvão, Silmara Aparecida de Lima; Lowe, Anna; Kitchen, Steve
Abstract: Introduction: The first external quality assessment (EQA) in Thrombosis and Haemostasis was elaborated over 20 years ago, and since then, several national and international EQA institutions have been established. Aim: Display the benefits of EQA programs. Methods: The spectrum of EQA action was evaluated ranges from improving the performance of the local laboratory to highlighting inadequate diagnostic tests that need to be replaced by new technologies. Results: The first result approach is related to a national management of quality in laboratories. In recent years, Brazil has invested in an EQA program to aid public policy in the laboratory area. During this period, a group of haemostasis laboratory specialists were invited to manage the results and help the Ministry of Health with applying these results as a strategy to improve laboratories. Thus, in collaboration with NEQAS‐BC, the University of Campinas – UNICAMP, established a Brazilian EQA program for Blood Coagulation. The second result approach is related to FVIII inhibitor assay performance evaluation, which is another type of EQA program benefit. Despite the assay being considered the gold standard to measure neutralised immunoglobulins for FVIII since 1975, over 40 years ago, the test still has a high coefficient of variation. Results from NEQAS‐BC and WFH IEQAS program demonstrate the inter‐laboratory variation across the United Kingdom over the last years and among emergent countries. Conclusion: The EQA programs have an important educational role in helping countries manage their public policy and in the international inquiry regarding the necessity of new technologies in haemostasis.